Turning the young and healthy patient into an elderly faster: A cascade of complications related to immobility (Indian Journal of Case Reports, 2024)
A 42-year-old individual presented with a ruptured left patellar ligament after playing basketball. After undergoing reconstructive orthopedic surgery, he sustained a posterior shoulder dislocation while using crutches, necessitating additional surgery. This combination of orthopedic injuries rendered the patient immobile and bedridden for several months, and immobility-related complications began to develop. Immobilism is a condition that physicians typically associate with elderly and neuropathic patients; however, little is said about this pathology when young and healthy patients who have experienced acute diseases are considered. With a review of the relevant literature, this article describes a peculiar succession of immobility-related complications.